2008
DOI: 10.1063/1.2903153
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light output of GaN-based light-emitting diodes with ZnO nanorod arrays

Abstract: We report enhanced light output of GaN-based light-emitting diodes (LEDs) with vertically aligned ZnO nanorod arrays. The ZnO nanorod arrays were prepared on the top layer of GaN LEDs using catalyst-free metalorganic vapor phase epitaxy. Compared to conventional GaN LEDs, light output of GaN LEDs with the ZnO nanorod arrays increased up to 50% and 100% at applied currents of 20 and 50mA, respectively. The source of the enhanced light output is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 18 publications
0
116
1
Order By: Relevance
“…This observation suggests that part of the junction emission might be directly waveguided to the tip of the nanowires. A similar setup has been investigated previously, employing a vertical ZnO nanorod array as a waveguiding mechanism for emission from a traditional GaN-based multiple quantum well (MQW) thin film LED [24,25]. Increases of 50% and 100% in light output at applied currents of 20 and 50 mA, respectively, were reported by An et al [24] whilst Chiu et al reported a 38.4% light output increase for a current injection of 200 mA.…”
Section: Nano Researchmentioning
confidence: 84%
See 1 more Smart Citation
“…This observation suggests that part of the junction emission might be directly waveguided to the tip of the nanowires. A similar setup has been investigated previously, employing a vertical ZnO nanorod array as a waveguiding mechanism for emission from a traditional GaN-based multiple quantum well (MQW) thin film LED [24,25]. Increases of 50% and 100% in light output at applied currents of 20 and 50 mA, respectively, were reported by An et al [24] whilst Chiu et al reported a 38.4% light output increase for a current injection of 200 mA.…”
Section: Nano Researchmentioning
confidence: 84%
“…A similar setup has been investigated previously, employing a vertical ZnO nanorod array as a waveguiding mechanism for emission from a traditional GaN-based multiple quantum well (MQW) thin film LED [24,25]. Increases of 50% and 100% in light output at applied currents of 20 and 50 mA, respectively, were reported by An et al [24] whilst Chiu et al reported a 38.4% light output increase for a current injection of 200 mA. However, our device geometry is different from these earlier experiments in that our waveguiding array is in fact part of the diode rather than an auxiliary component and therefore there is minimal loss of generated emission.…”
Section: Nano Researchmentioning
confidence: 99%
“…Though efficiency values are modest, ongoing optimization should show increases across all metrics as well as a reduction in the spread of device performance. NRAs have been previously highlighted as structures that may improve charge carrier injection or improve light out-coupling when used as external light extraction layers [42,53,54] . Here, the incorporation of an internal NRA, which can simultaneously exploit these potential advantages is presented with our best devices achieving brightness and efficiencies of 8600 cd/m 2 and 1.66 cd/A.…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of such advantages provided by the nanowires, the light can easily be extracted by multiple scattering. ZnO had a transmittance of over 90% in the visible range [414], so self-absorption by the nanowires should not be a major concern. Figure 49 shows the room temperature external quantum efficiency (calculated by from the ratio of the output light power to the input electrical power) versus d.c. injection current for the nanowire/thin film heterostructure LED [371].…”
Section: Light Extractionmentioning
confidence: 99%
“…Extensive efforts have been made to tackle this problem, such as roughening the emitting surface of the thin film [404,405], reshaping the geometry of the LED architecture [406,407], utilizing a resonant cavity [408], coupling with surface plasmons [409], fabricating photonic crystal structures [410,411], and using corrugated Bragg gratings [412]. Nanowire/ thin film heterostructures have been proposed to be a promising solution, considering the waveguiding properties of the nanowires that should enhance light extraction efficiency of the LED's [9,[413][414][415][416][417][418].…”
Section: Light Extractionmentioning
confidence: 99%